Effect of Solvent Polarity on the Extraction Yield of Antioxidants from Lactobacillus Supernatants: Effect of Solvent Polarity on the Antioxidant Extraction - Zahra Pourramezan; Rouha Kasra Kermanshahi; Mana Oloomi (Iranian Journal of Pharmaceutical Sciences, 2022)
There is increasing evidence to suggest that the Lactobacilli species possess antioxidant activities, however, there are a few reports of optimization of solvent systems for the separation of their antioxidant compounds by thin-layer chromatography. In the current study, we explore the efficiency of four organic solvents (aqueous, methanol, ethyl acetate, and n-hexane) for the extraction of antioxidant materials from Lactobacillus supernatants. According to the results, methanol extraction significantly increased the antioxidant properties of Lactobacillus supernatants. In addition, the methanol extract of Lactobacillus supernatants was fractionated using thin-layer chromatography (TLC). A solvent system consisting of methanol/chloroform is a promising approach for TLC analysis of Lactobacillus supernatant. The partial purification of the antioxidant components using thin-layer chromatography demonstrated a drastic rise in the antibacterial and antioxidant properties in comparison to the crude methanol extract of the same sample. In this study, the TLC fractionation of Lactobacillus extracellular materials was described for the first time. Further isolation and purification are essential to identify these bioactive compounds.